Osmanlı Devlet Adamlarından Hacı Âdil Bey’in II. Meşrutiyet Dönemindeki Faaliyetleri / Activities of Hacı Âdil Bey, who is the Ottoman Statesmen, in the Second Constitutional Period - Birbudak, Togay Seçkin (Journal of History Culture and Art Research, 2017)
Abstract Haci Adil (Arda) Bey, born in Lovech in 1869, was an important politician and jurist who held important positions in government offices both in the Ottoman Empire and in the Republic of Turkey. Throughout his career as a government official, which he started as a customs official in Yemen in 1890, he took several government offices in Yemen, Istanbul, and Thessaloniki for about 20 years and was inducted as the Governor of Edirne a short while after the proclamation of the Second Constitutionalist Period. Taking office as a senior manager within the party of Union and Progress following assume of governor of Edirne office, lasted for about a year, Haci Adil was appointed as Interior minister in 1912. He continued to hold critical offices during the Turco-Italian War, Balkan War and the First World War while the government was having hard times. He became interior minister once again in the government formed after the Sublime Porte Raid in 1913. HE was appointed as the governor of Edirne once again after the city was taken back during the Balkan War II, and held the office of chairperson of the Ottoman Parliament between the years 1915 and 1918. Arrested and exiled to Malta after end of First World War, Haci Adil lived the life of an exile abroad between the years 1919 and 1922. Returning home after his captivity in Malta, Haci Adil held the offices of the Governor of Adana and Bursa, lectured at the Ottoman University Darülfünun, and represented country on international courts. Haci Adil, who also held offices in Istanbul Municipality, died in 1935. This study gives information on the political and administrative activities of Haci Adil, who was one of the members of the headquarter of party of Union and Progress, during the Second Constitutional Period based on archive documents. Öz 1869 yılında Lofça’da dünyaya gelen Hacı Âdil (Arda) Bey, hem Osmanlı Devleti hem de Türkiye Cumhuriyeti zamanında mühim devlet görevlerinde bulunmuş önemli bir siyasetçi ve hukuk adamıdır. 1890 yılında Yemen’de gümrük memuru olarak başladığı devlet hizmetinde yaklaşık 20 yıl süre ile Yemen, İstanbul ve Selanik’te çeşitli memuriyetler üstlenmiş, II. Meşrutiyet’in ilanından kısa bir süre sonra Edirne Valisi olarak atanmıştır. Yaklaşık bir yıl süren Edirne Valiliği görevinden sonra İttihat ve Terakki Fırkası içerisinde üst düzey yöneticilik görevi alan Hacı Âdil Bey, 1912 yılında Dâhiliye Nâzırlığı’na getirilmiştir. Trablusgarp Savaşı, Balkan Savaşı ve I. Dünya Savaşı yıllarında devletin zor günlerinde kritik görevler almaya devam eden Hacı Âdil Bey 1913 yılında Bâb-ı Âlî Baskını sonrasında kurulan hükûmette bir kez daha Dâhiliye Nâzırı olmuş, II. Balkan Savaşı sırasında Edirne’nin geri alınmasının ardından bir kez daha bu şehre vali olarak atanmış, 1915-1918 yılları arasında da Meclis-i Mebusan Reisliği görevini yürütmüştür. I. Dünya Savaşı’nın sona ermesinin ardından tutuklanan ve Malta’ya sürgüne gönderilen Hacı Âdil Bey, 1919-1922 yılları arasında yurtdışında sürgün hayatı yaşamıştır. Malta esareti sonrasında yurda dönen Hacı Âdil Bey, Adana ve Bursa valilikleri görevlerinde bulunmuş, Dârülfünûn’da dersler vermiş ve uluslararası mahkemelerde ülkemizi temsil etmiştir. İstanbul Belediyesi’nde de görevler üstlenen Hacı Âdil Bey 1935 yılında vefat etmiştir. Söz konusu çalışmada İttihat ve Terakki Fırkası’nın merkez-i umumi azalarından olan Hacı Âdil Bey’in II. Meşrutiyet dönemindeki siyasî-idarî faaliyetleri hakkında arşiv belgeleri ekseninde bilgiler verilmektedir.